Forming Business Communication Skills and Interdisciplinary Approach to Study English - Kalandarova, Safiya (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
The paper covers some issues of interdisciplinary approach, defines the fundamental principles of its implementation and dwells upon actual program samples for using interdisciplinary links of ESP and profile disciplines in different fields of higher education.